Draft pronouncement 2011/5 IASB SMEIG draft Q&As - Lembaga Piawaian Perakaunan Malaysia (Kuala Lumpur : Malaysian Accounting Standards Board, 2011)
Cover issues on financing reporting standard for small and medium-sized entities from Exposure Draft (MASB ED72) and IFRS for SMEs General (Issue 1-3).
CD available at Koleksi Media
Title from CD-ROM.
System requirements : Microsoft Windows 98, Windows XP or later, 16MB RAM, screen resolution 800x600 or better, 1MB hard disk space, Microsoft Words, Adobe Acrobat Reader, JPEG.
Keywords: Small business; Financial statements; Accounting -- Standards